Lesbianidade e homossexualidade nas Atas da Sociedade Psicanalítica de Viena: contribuições à historiografia da psicanálise - Martins, Flávia Ripoli (2020)
The advent of psychoanalytic studies about lesbianity and homosexuality took place in a complex and plural context, under the influence of the pathological theses of psychiatry and the emergence of the first movements that claimed rights for women and the LGBTQI+ population. Although the social, cultural and theoretical aspects are fundamental for the understanding of the multiple arguments about these theme present in the history of psychoanalysis, so far many authors reduce the study of this subject to systematic readings of the Three essays on the theory of sexuality published by Freud in 1905, disregarding the plurality of treatments on this theme in his work and in the formulations of his collaborators. Based on these considerations, the present research aimed to study the inscriptions of the social and epistemological context of the Germanic Europe countries at the turn of the nineteenth century in the speeches of the first psychoanalysts on lesbianity and homosexuality. Using the Minutes of the Vienna Psychoanalytic Society as the main source, a theoretical and documentary research was carried out, analyzing the convergences, distensions and ruptures in the thoughts of these authors, based on an investigation that considered the heterogeneous elements and the influences of the different contexts on the psychoanalytic studies about the theme between the years of 1900 and 1920. The records of the minutes were investigated from the political, theoretical and clinical point of view and it was verified the existence of contextual inscriptions in the discourse of the first psychoanalysts, in metapsychology, in clinical practice and in the organization of the psychoanalytic movement. The investigation demonstrated how the speeches of the first psychoanalysts are the product of the tension between the transgressive potential of the concepts of unconscious and sexuality and the position of lesbians and homosexuals in the place and historical time in which psychoanalysis was developed